Levas Vladimirovas and the Beginning of the Scientific Reconstruction of the Königsberg Collections of Old Books - Walter, Axel Ernst (Bibliotheca Lituana, 2014)
This paper analyses Levas Vladimirovas’ article “Karaliaučiaus spaudos pradininkas Hansas Veinreichas ir pirmieji jo darbo tęsėjai (XVI–XVII a.)” from 1961 with the aim to demonstrate his pioneering significance for the study of Königsberg book and library history from its beginnings in the 16th century until today. The first part of the following paper recapitulates the decisive contribution of the Lithuanian research in the clearing up of the fate of the libraries of old Königsberg. The second part of this paper deals with Vladimirovas’ study that updates a tradition of book historical research for future book science. After 1945 Vladimirovas was not only the first scientist, who has worked so intensely and objectively with the Königsberg printing during the early modern times, he was perhaps the first researcher taking a closer look at the books from the former Königsberg libraries that after 1945 had been brought by expert groups of the Lithuanian Academy of Sciences at first to Kaunas, then to Vilnius.
Keywords: history of books; library history; history of science; Königsberg